Early Pleistocene stratigraphy, sedimentary environments, and formation contexts at Dmanisi in the Georgian Caucasus. Issue 172 (November 2022) - Ferring, Reid; Oms, Oriol; Nomade, Sebastien; Humphrey, John D.; Tappen, Martha; Coil, Reed; Shelia, Teona; Crislip, Peter; Chagelishvili, Rusudan; Kiladze, Gocha; Guillou, Hervé; Lordkipanidze, David
Abstract: The Early Pleistocene site of Dmanisi is now well known for its large number of fossils of early Homo erectus as well as associated artifacts and faunal remains, recovered mainly in pipe-related geologic features. Testing in the M5 unit 100 m to the west of the main excavations revealed a thick stratigraphy with no evidence of pipes or gullies, indicating that the geologic record at Dmanisi included spatially distinct sedimentary environments that needed further investigation. Here we report the results of a geoarchaeological program to collect data bearing on contexts and formation processes over a large area of the promontory. That work has defined over 40, 000 m 2 of in situ deposits with artifacts and faunas. Stratum A ashes bury the uppermost Mashavera Basalt, which we have dated to 1.8 Ma in the M5 block. The Stratum A deposits contain stratified occupations that accumulated quickly and offer good potential for recovery of in situ materials. Stratum B1 deposits above the A/B unconformity include all of the pipe and gully facies at Dmanisi, reflecting a brief but very intense phase of geomorphic change. Those deposits contain the majority of faunas and all of the hominin fossils. B1 slope facies offer excellent formation contexts away from the piped area, and all B1 deposits are sealed by Stratum B2 over the whole promontory. Strata B2 to B5 register a return to slope facies, with no further evidence of pipes or gullies. Those deposits also present excellent contexts for recovery of in situ occupations. Overall, Dmanisi's geologic history preserves an exceptional record of the activities and environmental context of occupations during the first colonization of Eurasia.